Spatial distribution of major and trace elements in a mining dam: sources and relationships among elements of environmental concern - Valente, Teresa Maria Fernandes (2016)
The concentration of major and trace elements have been determined in sediments samples taken from a mining dam, located in the upper area of the Tinto River basin (SW Spain). This dam, built to fulfil water needs for mining operations, is now completed clogged by accumulation of fine sediments. The results obtained for vertical and horizontal distribution of chemical elements showed highest average concentrations of Fe and Al, both with 10 %, and S (about 4 %). Toxic elements, such as As and Pb occur also with high concentrations (2515 and 5172 mg/kg, respectively). Determination of Enrichment Factors (EF) showed that sediments are enriched in elements related with the massive sulphide ore bodies and subsequent acid mine drainage processes. The elements Pb and As are that of major environmental concern, with enrichment factors higher than 10. Application of cluster analysis put in evidence the main sources of elements, allowing for the modelling of the origin of the accumulated matter. Therefore, in addition to contributions from sulphide (Fe, S) and gangue (Al, Mg), there are grouping of elements mobilized from phyllosilicates and feldspars, (e.g. Ca and K) as well as a specific group that reflects the geochemical affinity of rare earth elements in such acidic environment. Moreover, the way how elements are grouped testify the heterogeneity of geological contributions as well as the mining cycles over 4000 years of mining history in this worldwide known river basin.